IPTEKS PELATIHAN STRUCTURAL EQUATION MODELING PADA MAHASISWA MAGISTER PERGURUAN TINGGI SWASTA DI JAKARTA BARAT - Adhikara, Muhammad Fachruddin Arrozi; Lucius, Christophera R; Handayani, Sri; Sugiyanto, Sugiyanto; Endah, Nur Jannah (Universitas Esa Unggul, 2025)
Abstract This report identifies competency gaps for postgraduate students in social sciences, education, and management in applying Structural Equation Modeling (SEM) with AMOS software, which stems from weak statistical foundations—including understanding confirmatory factor analysis (CFA), pathway analysis, and goodness-of-fit index interpretation—as well as limited access to formal training and academic mentoring. This condition has implications for the inability to overcome technical problems such as multicollinearity, model imitation without conceptual understanding, and delay in completing studies. As a solution, training based on an integrative approach was implemented through lecture-based learning, hands-on workshops, and project clinics for three days which were designed applicatively using scaffolded learning and problem-based learning methods. The evaluation of the program showed significant success with a 35% increase in participants' understanding based on a comparison of pre-test and post-test, as well as 85% active participation, despite the technical constraints of AMOS licensing. The sustainability of the program is ensured through online discussion forums and monthly follow-up sessions. Development recommendations include training level stratification and implementation of blended learning, provision of pre-training modules, and institutional collaboration for licensing access, which collectively expect to improve participants' academic quality and career prospects on an ongoing basis. Keywords: training, problem based learning, think-aloud protocol AbstrakLaporan ini mengidentifikasi kesenjangan kompetensi mahasiswa pascasarjana ilmu sosial, pendidikan, dan manajemen dalam mengaplikasikan Structural Equation Modeling (SEM) dengan software AMOS, yang bersumber dari lemahnya fondasi statistik—meliputi pemahaman confirmatory factor analysis (CFA), analisis jalur, dan interpretasi indeks goodness-of-fit—serta terbatasnya akses pelatihan formal dan pendampingan akademik. Kondisi ini berimplikasi pada ketidakmampuan mengatasi masalah teknis seperti multikolinearitas, peniruan model tanpa pemahaman konseptual, serta keterlambatan penyelesaian studi. Sebagai solusi, diimplementasikan pelatihan berbasis pendekatan integratif melalui lecture-based learning, hands-on workshop, dan project clinic selama tiga hari yang dirancang secara aplikatif dengan metode scaffolded learning dan problem-based learning. Evaluasi program menunjukkan keberhasilan signifikan dengan peningkatan pemahaman peserta sebesar 35% berdasarkan perbandingan pre-test dan post-test, serta partisipasi aktif 85%, meskipun menghadapi kendala teknis lisensi AMOS. Keberlanjutan program dijamin melalui forum diskusi online dan sesi follow-up bulanan. Rekomendasi pengembangan mencakup stratifikasi level pelatihan, implementasi blended learning, penyediaan modul pra-pelatihan, dan kolaborasi institusional untuk akses lisensi, yang secara kolektif diharapkan dapat meningkatkan kualitas akademik dan prospek karir peserta secara berkelanjutan. Kata Kunci: pelatihan, problem based learning, think-aloud protocol